Prosthetic, orthodontic and implant-supported rehabilitation of five maxillary anterior teeth with alveolar bone loss - Odilon Guariza-Filho; Cristiano Miranda de Araujo; Angela Graciela Deliga Schroder; Orlando Motohiro Tanaka; Ricardo Kern; Antonio Carlos Ruellas
ABSTRACT Introduction: Treatment of maxillofacial injuries is complex and requires the establishment of a comprehensive and accurate diagnosis and correct treatment planning. Objective: The objective of this case report was to describe the re-treatment of a 27-year-old woman who was involved in a severe car accident that resulted in the loss of five anterior teeth and alveolar bone, and whose previous orthodontic and surgical treatments had been unsuccessful. Case report: In this case, the space for the missing mandibular molar was reopened to allow for rehabilitation. The positions of the mandibular incisors were improved. The right mandibular canine was moved to the mesial, allowing for correction of the Class II canine relationship on that side, and implants were placed to replace the maxillary anterior teeth. Conclusion: Anterior aesthetic and functional rehabilitation using a multidisciplinary approach was essential to improve the patient's facial aesthetics, to obtain great improvement in function and to achieve occlusal stability after 2 years of follow-up.